PENGARUH LINDI HASIL BIOKONVERSI SAMPAH BUAH OLEH LARVA BLACK SOLDIER FLY (Hermetia Illucens (L) TERHADAP PERTUMBUHAN SELADA BUTTERHEAD (Lactuca sativa var. capitata) DALAM SISTEM HIDROPONIK NUTRIENT FILM TECHNIQUE (NFT) - Balqisani Kurnia, Annissa
Hydroponics is an agricultural system without the use of soil media and can utilize narrow land that has become one of the alternative agricultural systems that are widely used in urban areas. High operational costs cause problems in the hydroponic system. The solution that can be done is to replace the hydroponic nutrient solution with organic solutions such as leachate solution from the bioconversion of organic waste by the Black Soldier Fly (BSF) larvae, Hermetia illucens. Research has been carried out to test the leachate solution as a hydroponic nutrient in Butterhead plants (Lactuca sativa var. Capitata) in the NFT hydroponic system. Butterhead (Lactuca sativa var. Capitata) was planted using the NFT hydroponic system with 60% AB Mix: Lindi 40%; AB Mix: 50%: Leachate 50%; AB Mix: 70%: Leachate 30%; AB Mix 40%: Leach 60%; AB Mix 100%; and Lindi 100%. The content of macronutrients and leachate micronutrients as nutrient solutions were analyzed at BALITSA. Observations were made on the number of leaves, wet and dry weight, chlorophyll content, fiber content, and vitamin C. The results of this study showed that leachate macronutrients and micronutrients had the elements needed for Butterhead growth (Lactuca sativa var. Capitata). The smaller the leachate content in a nutrient solution, the lower the content of inorganic souls (Na, K, Ca, Mg, Cl, S, F, N, phenols, and heavy metal compounds). The AB Mix (60%) and leachate (40%) treatments produced an average number of leaves 20 ± 4.70 strands, wet weight 46.033 ± 14.27 grams, dry weight 2.04 ± 0.39 grams, total chlorophyll 6.126 ± 0.047 mg / L, vitamin C content of 46.10 mg / 100 grams, and 0.95% fiber content. Based on the results of statistical tests conducted, this treatment was not significantly different from the control treatment (100% AB Mix). The AB Mix (60%) and Lindi (40%) treatments have primary macronutrient elements (N, P, and K) which can substitute the AB Mix solution, so it can be concluded that the composition of AB Mix (60%) and Lindi (40%) is the best composition for the growth of Butterhead (Lactuca sativa var. capitata).